3D Mapping and Ablation of Left Sided Atypical Atrial Flutter (Bangladesh Heart Journal, 2022)
Atypical atrial flutter has become amenable to catheter ablation with remarkable improvement in the acute and long-term efficacy of this therapy for this macro reentrant atrial arrhythmia. Here it was described a case of atypical atrial flutter which arises from left atrium and demonstrates the importance of a systematic approach to mapping and ablating atypical atrial flutter to prevent a recurrence of symptomatic arrhythmia. We also highlighted importance of 3D mapping which is a key tool for analysis and successful ablation.Bangladesh Heart Journal 2022; 37(2): 139-142